PERBEDAAN HASIL BELAJAR DENGAN MODEL PEMBELAJARAN MAKE A MATCH DAN TALKING STICK MATERI EKSKRESI DI MAN 2 MODEL MEDAN - Kartika Ayu Ningsih; Uswatun Hasanah; Ida Iriani (Jurnal Pelita Pendidikan, 2017)
This Research in MAN 2 Model Medan is aimed to know the difference of student learningoutcomes on Human Excretion System materials using Cooperative Learning Type Make a Match andCooperative Type Talking Stick. The type of research used is quasi experiment. Population in thisresearch is all student class XI IPA MAN 2 Model Medan that is counted 10 class. The sample of researchwas taken by two classes determined by purposive sampling technique, that is Experiment Class I (XI IPA4) and Experiment Class II (XI IPA 8) respectively as many as 43 and 41 students. The instrument used inthis study is a test in the form of objective tests of 25 questions each of which has been declared validand reliable. The results obtained that the average learning outcomes of students who are taught usingCooperative Learning Type Make a Match higher than the learning outcomes of students who taughtusing Cooperative Learning Talking Stick with the results of hypothesis testing obtained t count> t tabelis 2,009> 1,985 α  0,05 . The result of study of experiment class I obtained average postes of 90,60 ±7,30. While the result of study of experiment class II student average postes equal to 87,51 ± 6,88. Theresults showed that the student postes score reached KKM.Keywords:Cooperative, Make a Match, Talking Stick, Excretion.